Metabolism: a potential regulator of neutrophil fate - Yipeng, Zhou; Chao, Cao; Ranran, Li; Tingting, Pan; Hongping, Qu (Frontiers in Immunology, 2024)
Neutrophils are essential components of the innate immune system that defend against the invading pathogens, such as bacteria, viruses, and fungi, as well as having regulatory roles in various conditions, including tissue repair, cancer immunity, and inflammation modulation. The function of neutrophils is strongly related to their mode of cell death, as different types of cell death involve various cellular and molecular alterations. Apoptosis, a non-inflammatory and programmed type of cell death, is the most common in neutrophils, while other modes of cell death, including NETOsis, necrosis, necroptosis, autophagy, pyroptosis, and ferroptosis, have specific roles in neutrophil function regulation. Immunometabolism refers to energy and substance metabolism in immune cells, and profoundly influences immune cell fate and immune system function. Intercellular and intracellular signal transduction modulate neutrophil metabolism, which can, in turn, alter their activities by influencing various cell signaling pathways. In this review, we compile an extensive body of evidence demonstrating the role of neutrophil metabolism in their various forms of cell death. The review highlights the intricate metabolic characteristics of neutrophils and their interplay with various types of cell death.